The effect of weight, body mass index, age, sex , and race on plasma concentrations of subcutaneous sumatriptan: a pooled analysis - Munjal S; Gautam A; Rapoport AM; Fisher DM (Dove Medical Press, 2016)
Sagar Munjal,1 Anirudh Gautam,2 Alan M Rapoport,3 Dennis M Fisher4 1Department of Neurology Clinical Development and Medical Affairs, Dr. Reddy’s Laboratories Ltd, Princeton, NJ, USA; 2Pharmacokinetics, Modeling and Simulation & Bioanalysis, Dr. Reddy’s Laboratories Ltd, Hyderabad, India; 3Department of Neurology, The David Geffen School of Medicine, University of California, Los Angeles, Los Angeles, 4P Less Than, San Francisco, CA, USA Objective/background: Factors such as body size (weight and body mass index [BMI]), age, sex, and race might influence the clinical response to sumatriptan. We evaluated the impact of these covariates on the plasma concentration (Cp) profile of sumatriptan administered subcutaneously. Methods: We conducted three pharmacokinetic studies of subcutaneous sumatriptan in 98 healthy adults. Sumatriptan was administered subcutaneously (236 administrations) as either DFN-11 3 mg, a novel 0.5 mL autoinjector being developed by Dr. Reddy’s Laboratories; Imitrex® (Sumatriptan) injection 3 mg or 6 mg (6 mg/0.5 mL); or Imitrex STATdose 4 mg or 6 mg (0.5 mL). Blood was sampled for 12 hours to determine sumatriptan Cp. Maximum Cp (Cmax), area under the curve during the first 2 hours (AUC0–2), and total area under the curve (AUC0–∞) were determined using noncompartmental methods. Post hoc analyses were conducted to determine the relationship between these exposure metrics and each of body weight, BMI, age, sex, and race (categorized as white, black, or others). Results: Both weight and BMI correlated negatively with each exposure metric for each treatment group. Across all treatment groups, AUC0–2 for subjects with BMI less than or equal to median value was 1.03–1.12 times the value for subjects with BMI more than median value. For subjects with BMI less than or equal to median value receiving DFN-11, median AUC0–2 was slightly less than that for subjects with BMI more than median value receiving Imitrex 4 mg and larger than that for subjects with BMI more than median value receiving Imitrex 3 mg. Results were similar for the other exposure metrics and for weight. Exposure was higher in women than in men, which can be attributed in part to differences in weight. There was no relationship between exposure and age. For DFN-11, AUC0–2 and AUC0–∞ were lower in non-whites compared with whites; the ratio of median values was 0.84 and 0.89, respectively. A similar, nonstatistically significant, trend was observed in the other products (ratio of median values ranging from 0.84 to 0.89). Conclusion: Weight and BMI appear to be important covariates for sumatriptan exposure: subjects with lower values for either metric of body size have higher systemic exposure compared with subjects with higher values. Additional studies are required to determine if doses of subcutaneous sumatriptan may be adjusted based on BMI for comparable efficacy and a potentially improved tolerability profile. Keywords: sumatriptan plasma concentration, migraine, body size, BMI, obesity, age, sex, race